IDENTIFICATION AND DESIGNATION OF PHYSIOLOGIC RACES OF ASCOCHYTA RABlEl IN INDIA - SINGH, GURDIP (Indian Phytopathology, 2002)
Three hundred and forty eight isolates of Ascochyta rabiei collected from the North Indian States were broadly categorized into 23 groups on the basis of morphology. These were further re-arranged to 15 based on morphological and cultural characters. Pathogenicity of representative isolates from each of the 15 groups was tested and isolate No. 6 and 23 were a virulent. Reaction type of the remaining 13 isolates was studied on 12 differential chickpea lines and 12 races, viz. 1(3072), 2(4080), 3(3844), 4(3492), 5(3522), 6(3968), 7(4064), 8(3560), 9(3744), 10(3904), 11(4080) and 12(1744) were identified. Race 11(4088) was the most virulent and 12 (1744) was the least virulent.